(untitled) (Ágora de Heterodoxias, 2019)
The document presents a perspective related to the pedagogical and didactic use of mobile technologies, due to the high levels of appropriation of the Smartphone by young people, as a source of innovative and significant learning, for the strengthening of competences related to the socio-cultural identities. For this, the principles set out by the United Nations (UN) and its 2030 Agenda on the Sustainable Development Goals are considered, as well as the UNESCO project on mobile learning (2019). This document points quality education, inclusive, accessible, delocalized and ubiquitous, strengthened with innovative mechanisms to interact with heritage content, as a central element of sustainability and the construction of identities with technological mediations and pedagogical criteria. This is based on the assumption that information and communication technologies and mobile devices offer possibilities to innovate in the pedagogies and didactic strategies that are established inside and outside the classroom and that can be used to teach cultural heritage in university contexts. The conclusions point to the practice of multiple didactic strategies impregnated with innovation and dynamism, to generate significant and lifelong learning.